Про особливості прийому препаратів вітаміну D3 при лікуванні вірусних інфекцій - Крісанова, Наталія Вікторівна; Krisanova, N. V. (My University, 2024)
The work provides existing facts in modern scientific literature about vitamin D3 and its derivatives (calcidiol and calcitriol): synthesis, metabolism, transport in the blood, the possibility of deposition, biochemical and physiological effects of the active form of D3 - calcitriol. The question of calcitriol influences the human immune system in condition of increased concentration of its precursor - vitamin D3 is especially considered.
About features vitamin D3 drugs use in the treatment of viral infections